The Registration of Interfaith Marriages in The Determination of The Medan District Court (Study of Determination Decision No. 1350/PDT.P/2022/PN.MDN) - Damanik, Putra Brima Sakti; Sitorus, Nanang Tomi; Ramadhan, Muhammad Citra (Journal Analytica Islamica, 2025)
The phenomenon of interfaith marriage in Indonesia reflects the complexity of the relationship between positive law, human rights, and religious norms, particularly within a multicultural society. This article examines the practice of registering interfaith marriages through judicial determination, focusing on the case study of Determination No. 1350/Pdt.P/2022/PN.Mdn by the Medan District Court. Using a normative juridical approach supported by empirical data, this study analyzes the applicable legal provisions, judicial considerations, and insights from the perspective of Islam and maqashid al-shari’ah. The findings reveal that the registration of interfaith marriages through court rulings represents a legal response to normative gaps that fail to accommodate the needs of a pluralistic society. In the context of Islamic law, a maslahah-based approach is employed to interpret administrative registration without legitimizing the practice religiously. Meanwhile, from the perspective of state law, the court’s decision demonstrates the application of progressive legal principles and the protection of citizens’ civil rights. Therefore, such rulings serve as an important precedent for reforming marriage registration policies to be more humane, contextual, and aligned with the principles of social justice in a democratic legal state.